1995
DOI: 10.1111/j.1365-2362.1995.tb01733.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin acts as a radical scavenger and is oxidized to a dimer during the respiratory burst of human mononuclear and polymorphonuclear phagocytes*

Abstract: Isolated human mononuclear and polymorphonuclear phagocytes were stimulated in the presence and absence of serotonin (5-HT), the major secretory product of activated platelets, and the release of reactive oxygen metabolites during the respiratory burst was assessed by luminol-enhanced chemiluminescence. In the presence of 5-HT, a dose-dependent suppression of the chemiluminescence signal occurred, irrespective of the stimulus used to elicit the respiratory burst. A similar suppression of luminol-enhanced chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Some groups propose direct effects of serotonin on neutrophils in oxidative burst whereas others attribute serotonininduced effects to the release of messengers from endothelial cells or to direct extracellular effects of serotonin. 29,30 Serotonin did not induce significant superoxide production in an investigation of human neutrophils, 31 but decreased the production of reactive oxygen species in other studies. 32 Recently, it was reported that serotonin inhibited the oxidative burst in total leukocyte preparations from human blood, but not in isolated neutrophils.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Some groups propose direct effects of serotonin on neutrophils in oxidative burst whereas others attribute serotonininduced effects to the release of messengers from endothelial cells or to direct extracellular effects of serotonin. 29,30 Serotonin did not induce significant superoxide production in an investigation of human neutrophils, 31 but decreased the production of reactive oxygen species in other studies. 32 Recently, it was reported that serotonin inhibited the oxidative burst in total leukocyte preparations from human blood, but not in isolated neutrophils.…”
Section: Discussionmentioning
confidence: 79%
“…[29][30][31][32][33][34] To date, the existence or nonexistence of serotonergic components in neutrophils has not been established. Some groups propose direct effects of serotonin on neutrophils in oxidative burst whereas others attribute serotonininduced effects to the release of messengers from endothelial cells or to direct extracellular effects of serotonin.…”
Section: Discussionmentioning
confidence: 99%
“…Some other tryptophan-derived metabolites were also found to display potent antioxidative properties in vitro as well as in vivo (Christen et al, 1990;Huether et al, 1990;Jovanovic and Simic, 1985;Liu and Mori, 1993;Pieriefiche et al, 1993;Schuff-Werner et al, 1995). Serotonin (5-hydroxytryptamine, 5-HT) and melatonin (N-acetyl-5-methoxytryptamine, MLT) are well known as physiologically important neurotransmitters involved in fundamental biological functions such as circadian rhythm, sleep control, reproduction, control of blood pressure, and aging.…”
Section: Phagocyte-specific Antioxidative Defense Mechanismsmentioning
confidence: 99%
“…We proposed that serotonin may act as an important endogenous scavenger of ROS generated during the respiratory burst of PMN and monocytes protecting host tissue as well as the phagocyte itself from oxidative damage (Schuff-Werner et al, 1995;Schuff-Werner and Splettstoesser 1999). Numerous findings concerning the interaction of 5-HT with oxygen radicals are consistent with this hypothesis: Serotonin was shown to protect isolated DNA from lesions induced by UV light or gamma-irradiation (Ivanova and Fraikin, 1985); its synthesis is induced by UV-radiation in yeasts, rendering them more resistant to challenge with UV-light or gamma-irradiation ("photoprotection") (Fraikin et al, 1981).…”
Section: Phagocyte-specific Antioxidative Defense Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation